Influence of Social Media on Purchasing Decision in Chennai - Ratchaya, S. Kiruti; Sreeya, B. (Recent Progress in Science and Technology Vol. 9, 2023)
The study's goals are to determine whether social media has an impact on the general public, to assess the degree to which reviews on social media affect people's purchase decisions, to look into the relationship between the influence of advertisements on consumers' purchase decisions and marital status, and to examine the relationship between social media product advertisements and respondent age. Making a purchase is a fundamental leadership activity that customers use to display their interactions both before and after making a purchase of a good or service. It is frequently seen as a particular kind of cost-benefit analysis given the potential of various alternatives. A few basic cases include shopping and choosing what to eat. This showcase of basic leadership is a mental process. The study used 1450 respondents for the purpose of understanding the buying decision. Chi-square, independent t test and correlation are the various tests used in this research. According to the study, men and women view social media advertising from different angles. Customers are less concerned about their purchase decisions as income levels rise. Teenagers only are targeted by the majority of social media product marketing. Relationship status has no bearing on how effective advertising is in influencing consumer decisions.